Uptake of glycerol 3-phosphate and some of its analogs by the hexose phosphate transport system of Escherichia coli. - Guth, A (1980)
The hexose phosphate transport system transported glycerol 3-phosphate and its analogs 3,4-dihydroxybutyl-1-phosphonate, glyceraldehyde 3-phosphate, and 3-hydroxy-4-oxobutyl-1-phosphonate.